(untitled) (International Seven Journal of Multidisciplinary, 2026)
Celiac disease is a chronic inflammatory autoimmune disorder triggered by gluten ingestion in genetically predisposed individuals, with a significant impact on the pediatric population, particularly on growth and development. Gluten-induced enteropathy in childhood damages the small intestinal mucosa, causing malabsorption of essential nutrients and ultimately leading to growth failure, delayed puberty, and nutritional deficiencies. This study aims to discuss the therapeutic management of pediatric celiac disease, with an emphasis on monitoring growth and development as central components of treatment. It is a narrative literature review conducted through a search in the PubMed database using standardized descriptors and included publications from the last five years addressing celiac disease, childhood, diagnosis, and treatment. These findings reveal that the clinical presentation of celiac disease during childhood is heterogeneous, including gastrointestinal and extra-intestinal manifestations, which can delay diagnosis and affect growth. Early recognition, based on serological evidence and, when appropriate, duodenal biopsy, is crucial for the effective implementation of a gluten-free diet, the only treatment currently proven effective. Strict adherence to the diet is also a key factor leading to clinical, nutritional recovery and catch-up growth, particularly in the initial months after diagnosis. However, the challenges associated with dietary adherence further emphasize the need for multidisciplinary follow-up. Systematic monitoring of growth, pubertal development, nutritional status, and serology is an essential aspect of the clinical management of pediatric celiac disease and is crucial for a favorable prognosis and the prevention of short- and long-term complications.